La conversación psicoanalítica: su utilidad en salud mental. - GUILLAMÓN, RAFAEL ARROYO (Revista de la Asociación Española de Neuropsiquiatría)
The limited presence of psychoanalysis in public mental health services invites a review of its practice. This article postulates that the psychoanalytic conversation is a relevant modification of classical psychoanalysis of great utility for the current challenges of this field of care. Based on a selective review of recent literature and the author's clinical experience, it defines the characteristics of the psychoanalytic interview and which modifications might bring it into line with public mental health work. It is concluded that a critical renewal of psychoanalysis makes it more accessible and compassionate, consolidating it as an essential therapeutic tool sensitive to the changing needs of society.